MARKETING MIX COMMUNICATION DALAM PENJUALAN PRODUK DAN JASA FINDTIME STUDIO PHOTOGRAPHY - CAHYONO, EFENDI DWI (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2021)
The convenience of digital technology makes photography easy to do so that almost everyone has an interest in taking photos with a digital camera. Therefore, it makes a competitor in the photo studio. With this competition, an appropriate marketingcommunication strategy is needed. This study aims to determine the marketing mix communication in the sale of Findtime Studio Photography products or services. The marketing communications mix is a special blend of tools that companies use to ensure the value of communications and build relationships with consumers. The marketing communication mix is the best strategy combination of advertising variables, personal selling, and other promotional tools planned to achieve the objectives of the sales program. Data collection techniques were conducted by interviews with the owner of Findtime Studio Photography. This study indicates that Findtime Studio Photography uses a marketing mix communication model to support product/service sales, including advertising, direct marketing, sales promotion, personal selling, interactive marketing, and public relations.